2013
DOI: 10.1152/jn.00677.2012
|View full text |Cite
|
Sign up to set email alerts
|

Firing rate and pattern heterogeneity in the globus pallidus arise from a single neuronal population

Abstract: Deister CA, Dodla R, Barraza D, Kita H, Wilson CJ. Firing rate and pattern heterogeneity in the globus pallidus arise from a single neuronal population. J Neurophysiol 109: 497-506, 2013. First published October 31, 2012 doi:10.1152/jn.00677.2012.-Intrinsic heterogeneity in networks of interconnected cells has profound effects on synchrony and spike-time reliability of network responses. Projection neurons of the globus pallidus (GPe) are interconnected by GABAergic inhibitory synapses and in vivo fire continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Evidence exists for the contribution of intrinsic mechanisms to variability in the cycle-to-cycle period in spontaneously active vertebrate neurons. Long-term (minute to hours) trends in the spontaneous spike rate have been observed in neurons in the external segment of the globus pallidus (GPe) in anesthetized rats and brain slice preparations (Deister et al 2012). These long-term fluctuations are distinguished from cycle-to-cycle jitter in the interspike interval (ISI) by calling the slow fluctuations "wander" in the period.…”
Section: New and Noteworthymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence exists for the contribution of intrinsic mechanisms to variability in the cycle-to-cycle period in spontaneously active vertebrate neurons. Long-term (minute to hours) trends in the spontaneous spike rate have been observed in neurons in the external segment of the globus pallidus (GPe) in anesthetized rats and brain slice preparations (Deister et al 2012). These long-term fluctuations are distinguished from cycle-to-cycle jitter in the interspike interval (ISI) by calling the slow fluctuations "wander" in the period.…”
Section: New and Noteworthymentioning
confidence: 99%
“…These long-term fluctuations are distinguished from cycle-to-cycle jitter in the interspike interval (ISI) by calling the slow fluctuations "wander" in the period. Elegant experiments (Deister et al 2012) using paired recordings of multiple neurons revealed that the spike rates of each cell wandered independently. This experimental design eliminates temperature or other variables that the cells have in common as the source of the wander.…”
Section: New and Noteworthymentioning
confidence: 99%
“…Since neurons firing at widely different rates do not tend to synchronize with each other, this cellular heterogeneity may make the GPe less susceptible to synchronized inputs. Deister et al [2013] therefore describe a powerful mechanism of decorrelation in the healthy GPe. However, changes in this heterogeneity after dopamine depletion have not yet been investigated.…”
Section: Cellular Heterogeneitymentioning
confidence: 90%
“…In contrast, studies using healthy rat brain slices described three electrophysiological subgroups of neurons in the GP Stanford, 2000, Bugaysen et al, 2010]. However, other in vitro studies reported no clear qualitative electrophysiological differences amongst GP neurons and challenge the existence of distinct GP neuron types [Chan et al, 2004, Hashimoto and Kita, 2006, Günay et al, 2008, Chan et al, 2011, Deister et al, 2013.…”
Section: Intrinsic Gpe Structurementioning
confidence: 99%
See 1 more Smart Citation